Time-varying Cointegration Models and Exchange Rate Predictability in Korea - Soo Kyung Park; Choel Beom Park (KDI Journal of Economic Policy, 2015)
We examine the validity of popular exchange rate models such as the purchasing power parity (PPP) hypothesis and the monetary model for Korean won/US dollar exchange rate. Various specification tests demonstrate that Korean data are more favorable for both models based on time-varying cointegration coefficients as compared to those based on constant cointegration coefficients. When the abilities to predict future exchange rates between those models based on timevarying cointegration coefficients are compared, an in-sample analysis shows that the time-varying PPP (monetary model) has better predictive power over horizons shorter (longer) than one year. Results from an out-of-sample analysis indicate that the time-varying PPP outperforms models based on constant cointegration coefficients when predicting future exchange rate changes in the long run.
Keywords: F37; F41; 330; Exchange rate; Monetary model; Predictability; Purchasing power parity; Timevarying cointegration